Scientific representation paradoxes of perspective - Van Fraassen, Bas C., 1941- (Oxford : Oxford University Press, 2008)
The author presents an original exploration of how we represent the world. He investigates the nature of representation in both science and art, defends a distinctive position in contemporary philosophy of science, and illuminates the complex relationship between appearance and reality.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Science -- Philosophy